Nancy Drew Mystery Stories: The Secret of the Old Clock - Book 1 - Keene, Carolyn (New York : Grosset & Dunlap, 1987)
Nancy Drews keen mind is tested when she searches for a missing will.
760
Accelerated Reader
Keywords: Drew, Nancy (Fictitious character) -- Juvenile fiction; Wills -- Juvenile fiction; Fiction; Fiction; Mysteries, Detective fiction